A techno-economic comparison of ground-coupled and air-coupled heat pump system for space cooling - Esen, Hikmet; Inalli, Mustafa; Esen, Mehmet (Pergamon-Elsevier Science Ltd, 2007)
This paper reports a techno-economic comparison between a ground-coupled heat pump (GCHP) system and an air-coupled heat pump (ACHP) system. The systems connected to a test room in Firat University, Elazig (38.41 degrees N, 39.14 degrees E), Turkey, were designed and constructed for space cooling. The performances of the GCHP and the ACHP system were experimentally determined. The experimental results were obtained from June to September in cooling season of 2004. The average cooling performance coefficients (COPsys) of the GCHP system for horizontal ground heat exchanger (HGHE) in the different trenches, at 1 and 2 m depths, were obtained to be 3.85 and 4.26, respectively and the COPsys of the ACHP system was determined to be 3.17. The test results indicate that system parameters can have an important effect on performance, and that GCHP systems are economically preferable to ACHP systems for the purpose of space cooling. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: heat pump; ground-coupled; air-coupled; techno-economic analysis; cooling; Turkey